Declaration of nullity for the divorced and remarried couples: A Study Case in Manado Diocese - Albertus Sujoko; Gregorius Hertanto Dwi Wibowo (Asosiasi Ahli Filsafat Keilahian Indonesia, 2022)
This research seeks a permanent juridical solution for the pastoral problem of catholic split marriages. Many such couples need the Catholic Church's intervention to give way out of their family problem. And there is indeed a solution provided by Pope Francis with the reform of Canon Law regarding the issue of divorce and remarried couples of Catholic families. The research method is identifying and documenting what has been done in the diocese of Manado by Fr. Jan van Paassen and studying his approach to dealing with families needing help. Bibliographical research indicates the method of Fr. Jan van Paassen in dealing with the problem. It has a solid foundation and a reasonable argumentation which may be accepted by the authority of the Church based on the Calon Law itself. May this research help solve the pastoral problem of the catholic split marriage on the one hand. On the other side, the indissolubility of marriage remains the permanent teaching of the Catholic Church.